Endoscopic stapling in comparison to laparoscopic fundoplication for the treatment of gastroesophageal reflux disease. Issue 1 (7th April 2013) - Danalioglu, Ahmet; Cipe, Gokhan; Toydemir, Toygar; Kocaman, Orhan; Ince, Ali Tuzun; Muslumanoglu, Mahmut; Senturk, Hakan
<x xml:space="preserve">Abstract</x> Background The SRSTM Endoscopic Stapling System (Medigus Ltd, Omer, Israel) is a novel method for the treatment of gastroesophageal reflux disease (GERD). The present study assessed the safety and efficacy of SRS compared with laparoscopic anti‐reflux surgery (LARS). Patients and Methods Of 27 participants, 11 underwent SRS and 16 LARS. Symptoms were assessed using Velanovich GERD–health‐related quality of life (GERD‐HRQL) scores. The groups were compared in reference to operation time, improvement in GERD‐HRQL scores, and postoperative course. Chi‐squared and Mann–Whitney‐U‐tests were used for statistical analysis. Results Of 16 (59.3%) male and 11 (40.7%) female patients, mean age was 39.6 (range: 24–60) years and mean body mass index was 26.2 kg/m2. Both groups were statistically similar. An esophageal perforation observed in the SRS group completely recovered after over‐the‐scope clipping. Procedure times for SRSand LARS were 89 and 47 min, respectively (P < 0.05). Mean discharge time was longer for SRS than LARS (3 days vs 1.2 days, P < 0.05). However, this difference disappeared with the exclusion of a complicated patient with long hospitalization in the SRS group. During 6 months mean follow up, proton‐pump inhibitor use was insignificantly higher in the SRS group (P > 0.05). Mean GERD‐HRQL scores dropped in 87% and in 64% of patients (P > 0.05) from 29.3 to 4.1 and from 24.8 to 8.9 (P = 0.016) in LARS and SRS groups, respectively. Conclusion The short‐term results of SRS are promising. The forthcoming new‐generation devices and increasing experience may further improve efficacy and decrease untoward effects.